Abiraterone and Increased Survival in Metastatic Prostate Cancer - de Bono, Johann S; Logothetis, Christopher J; Molina, Arturo; Fizazi, Karim; North, Scott; Chu, Luis; Chi, Kim N; Jones, Robert J; Goodman, Oscar B; Saad, Fred; Staffurth, John N; Mainwaring, Paul; et al. (The New England journal of medicine, 2011)
In this study, abiraterone acetate inhibited androgen synthesis and prolonged survival by 4 months among men with castration-resistant prostate cancer that had progressed with docetaxel chemotherapy. For the past 70 years, depleting or blocking the action of androgens has been the standard of care for men with advanced prostate cancer. 1 Androgen deprivation results in a decrease in the concentration of prostate-specific antigen (PSA) as well as tumor regression and relief of symptoms in most patients, but the response to treatment is not durable in patients with advanced cancer, and with time, PSA concentrations increase, indicating reactivated androgen-receptor signaling and a transition to a castration-resistant state that is invariably fatal. 2 Many endocrine therapies have been evaluated in these patients, but none have prolonged survival. 3 Three nonhormonal systemic . . .